Penerapan Model Pembelajaran Inkuiri Bebas Upaya Meningkatkan Prestasi Belajar Matematika Dasar Menggunakan Aplikasi Microsoft Excel 2010 - Qurniati, Nofi; Fredricka, Jhoanne; Prahasti (LPPM UNIKA Santo Thomas Medan, 2022)
This research is conducted based on observation that learning about mathematics in the class is always use convensional method. This research is sopposed to know learning achievement in the free Inquiry learning model with Microsoft Excel 2010 application student SMA Muhammadiyah 1 Bengkulu. The methodology that is use classroom action research, 1. The application of the free inquiry learning model using the Microsoft Excel 2010 application can improve student achievement in mathematics, 1. The application of the free inquiry learning model using the Microsoft Excel 2010 application can improve student and effective in improving student achievement. The results obtained from the pre-test to the post-test in each cycle from the t-test results in each cycle showed that there was a significant difference in student achievement after the application of the free inquiry learning model using the Microsoft Excel 2010 application.